Dynamic structure mediates halophilic adaptation of a DNA polymerase from the deep‐sea brines of the Red Sea. Issue 6 (24th January 2018) - Takahashi, Masateru; Takahashi, Etsuko; Joudeh, Luay I.; Marini, Monica; Das, Gobind; Elshenawy, Mohamed M.; Akal, Anastassja; Sakashita, Kosuke; Alam, Intikhab; Tehseen, Muhammad; Sobhy, Mohamed A.; Stingl, Ulrich; et al.
ABSTRACT: The deep‐sea brines of the Red Sea are remote and unexplored environments characterized by high temperatures, anoxic water, and elevated concentrations of salt and heavy metals. This environment provides a rare system to study the interplay between halophilic and thermophilic adaptation in biologic macromolecules. The present article reports the first DNA polymerase with halophilic and thermophilic features. Biochemical and structural analysis by Raman and circular dichroism spectroscopy showed that the charge distribution on the protein's surface mediates the structural balance between stability for thermal adaptation and flexibility for counteracting the salt‐induced rigid and nonfunctional hydrophobic packing. Salt bridge interactions via increased negative and positive charges contribute to structural stability. Salt tolerance, conversely, is mediated by a dynamic structure that becomes more fixed and functional with increasing salt concentration. We propose that repulsive forces among excess negative charges, in addition to a high percentage of negatively charged random coils, mediate this structural dynamism. This knowledge enabled us to engineer a halophilic version of Thermococcus kodakarensis DNA polymerase.—Takahashi M., Takahashi, E., Joudeh, L. I., Marini, M., Das, G., Elshenawy, M. M., Akal, A., Sakashita, K., Alam, I., Tehseen, M., Sobhy, M. A., Stingl, U., Merzaban, J. S., Di Fabrizio E., Hamdan S. M., Dynamic structure mediates halophilic adaptation of a DNA polymerase from the deep‐sea brines of the Red Sea. FASEB J. 32, 3346–3360 (2018). www.fasebj.org